On your mark, get set, laugh! ; Friends for never / by Nancy Krulik ; illustrated by John & Wendy - Krulik, Nancy E. (New York : Grosset & Dunlap, 2004)
On your mark, get set, laugh! Katie thinks the fourth grade is awesome! She$1 (Bs making lots of friends and just joined the new track team. But Katie thinks her new track coach is simply unfair! She only puts in the fastest runners, leaving Katie on the bench. But when Katie turns into Coach Debbie, she decides to give all the kids a chance.s
Friends for never. Katie and Suzanne have been best friends for ever. But now Suzanne$1 (Bs become a total snob! Katie has had enough, and declares that she and Suzanne are now friends for never! Then Katie turns into Suzanne at a very important moment$1 (Bjust as Suzanne is about to make her modeling debut! Will Katie$1 (Bs walk down the runway ruin their friendship forever?s
The two stories are bound inverted, as issued.
Keywords: Children's stories; Fiction